2012
DOI: 10.1515/znc-2012-5-611
|View full text |Cite
|
Sign up to set email alerts
|

A PEGylation Technology of L-Asparaginase with Monomethoxy Polyethylene Glycol-Propionaldehyde

Abstract: Polyethylene glycol (PEG) conjugation technology has been successfully applied to improve the performance of protein drugs. In this study, L-asparaginase was N-terminal sitespecifi cally modifi ed by alkylating PEG with monomethoxy polyethylene glycol-propionaldehyde (mPEG-ALD 20000 ). The optimum reaction parameters were determined as pH 5.0, a molar ratio of mPEG-ALD 20000 to L-asparaginase of 10:1, a reaction time of 16 h and temperature of 25 °C. PEG-L-asparaginase (PEG-L-ASNase) was isolated and purifi ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Interestingly, the immunogenicity of PEGylated TPPs may be reduced due to steric hindrance caused by PEG, which can impede immune recognition (Harris et al, 2001;Shi et al, 2022). For instance, PEGylation of asparaginase could eliminate its antigenicity (Abuchowski et al, 1977;Duval et al, 2002;Molineux, 2003;Wang et al, 2012).…”
Section: Biological Properties Of Peg and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the immunogenicity of PEGylated TPPs may be reduced due to steric hindrance caused by PEG, which can impede immune recognition (Harris et al, 2001;Shi et al, 2022). For instance, PEGylation of asparaginase could eliminate its antigenicity (Abuchowski et al, 1977;Duval et al, 2002;Molineux, 2003;Wang et al, 2012).…”
Section: Biological Properties Of Peg and Its Derivativesmentioning
confidence: 99%
“…However, due to short half-life and antigenicity, L-asparaginase induces severe allergic reactions (Chung, 2010). PEGylated L-asparaginase has the ability to shield antigenic epitopes, reduce immunogenicity, prolong plasma retention time, and decrease proteolysis and renal excretion (Duval et al, 2002;Wang et al, 2012;Molineux, 2023). Clinical trials of PEGylated L-asparaginase began in 1984 and it was found to be safe for patients who had previously experienced allergic reactions to E. coli or Erwinia L-asparaginase (Graham, 2003).…”
Section: Pegylated Asparaginasementioning
confidence: 99%